Proportion of Wheat (Triticum aestivum L.) and Kimpul (Xanthosoma sagittifolium) Flours and Dragon Fruit (Hylocereuscostaricensis) Substitution on Wet Noodle - Ika Rahmawati; Fungki Sri Rejeki; Diana Puspitasari; Endang Retno Wedowati (Food Science and Technology Journal (Foodscitech), 2022)
Wet noodle is a food product that is liked by all levels of society. The main ingredient for making wet noodle is wheat flour which must be imported from other countries. For this reason, it is necessary to look for other alternative raw materials, namely kimpul flour. Red dragon fruit can be used to increase nutritional value because it contains antioxidant and improves product appearance because it contains natural dyes. The purpose of the study was to determine the effect of the proportion of wheat and kimpul flours, as well as the concentration of dragon fruit on the quality of dragon fruit wet noodle. This study used a factorial randomized block design (RBD) with the first factor being the proportion of wheat flour and kimpul flour (T1 = 40%:60%, T2 = 50%:50% and T3 = 60%:40%) and the second factor was dragon fruit concentration (N1 = 20% and N2 = 30%) with 3 replications. The results showed that the proportion of wheat flour and kimpul flour had a significant effect on protein content, elasticity, and organoleptic tests. While the concentration of dragon fruit significantly affected the water content, carbohydrate content, elasticity, and organoleptic tests. The conclusion of this research was the treatment of T3N2 (proportion of wheat flour and kimpul flour 60%: 40% and dragon fruit concentration 30%) became the selected treatment with parameters of water content 48.51%, ash content 1.72%, protein content 6 0.04%, fat content 2.64%, carbohydrate content 41.09%, and elasticity of 0.39, and has a total preference percentage of 100% color, 96.7% aroma, 100.0% taste and 96.7% texture.